Comparison of Amendments to the Value Added Tax Law between Indonesia and Malaysia to Regulate Murabaha Transactions - Adi Purwanto, Thesa (International Journal of Engineering and Technology, 2018)
Islamic banking in their activity base on Islamic principles that is agreement regulation on Islamic Law between Bank and others to saving and or financing an activity or business which suit Islamic role. There are several forms of financing, such as financing on sharing profit principle (mudharabah), financing on participation principle (musyarakah), transaction goods principle which get profit (murabaha), financing capital goods on rent principle without choice (ijarah), or with transfer authority over the rent goods from bank to others (ijarah wa iqtina). Furthermore, development of Islamic banking either in Indonesia or Malaysia must be followed with new law and regulation from their government, especially for rules on taxation over transaction on Islamic banking. This is critical because there are different interpretation and argumentation between practitioners of Islamic banking and the government about the subject of Value Added Tax on murabaha transaction. This research used a qualitative approach, using literature study, which emphasizes books as an object and field study with collecting data by interviewing and also using secondary data. As a result, both Indonesia and Malaysia has undergone essential steps to provide Islamic finance with appropriate banking and tax regulations that have succeeded in supporting the Islamic financial system.Â Â